Operations research and management science - Temirkhanova, Sapura (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
Place of Infographics in media market among developed modern technologies and enforcing to the human attraction is discussed.Findings have shown that relations between struggle of mass media for the human attraction in media market and diverseness of news are quite complicated. Purpose of this article: importance of Infographics in our present lives from the point of variousness as well as fairness and utilization of new methods in mass media, learning of them. In first part of the article: about Infographics and general opinions concerning scientists data who researched it, basic conceptions; at next part: current significance of Infographics in media market; lastly: modern methods, simple descriptions, increasing of Infographics's place in media